Effects of playing violent computer games on emotional desensitization and aggressive behavior - Arriaga, P.; Monteiro, M.; Esteves, F. (Journal of Applied Social Psychology, 2011)
his study analyzed the effects of playing a violent computer game on emotional desensitization and aggressive behavior. College students (N = 58) were randomly assigned to play a violent game (VG) or a nonviolent game (NVG), and then were exposed to a set of emotional pictures. Participants' physiological responses were recorded, and the Self-Assessment Manikin scale was used to assess affective valence and arousal while viewing the pictures. Participants were then asked to replay the game, after which aggressive behavior was measured. Participants' violent game habits (VGH) were also measured. We found that VG playing interacted with participants' VGH to influence aggression, and that self-reported valence mediated this effect by lowering the feelings of pleasure and displeasure toward emotional stimuli.